Human resource management - time to exorcize the militant tendency - Hart, Tim J. (1993)
Abstract: The ascendancy of human resource management (HRM) in recent years in the UK has been a major issue for both practicing managers and academics interested in this field. Does not seek to review the mass of material already published on this topic; nor to take a balanced analytical approach emanating from research. Takes an openly polemical stance, producing a damning indictment of the impact of HRM on the way in which employees are treated in work organizations and the wider social and ecological consequences if HRM practices are allowed to continue unabated.